Pengaruh Motivasi Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Karyawan Pada PT Delta Systech Indonesia Di Bogor - Haliza Nurahma; Ibnu Sina (JURNAL KONSISTEN, 2025)
Purpose. This research aims to determine the influence of motivation and non physical work environment on employee performance at PT. Delta Systech Indonesia in Bogor. Methods. This research uses quantitative methods with an associative approach. The research population was all 56 employees, and the sample used was the entire population. The data analysis methods used include simple linear regression test, multiple linear regression, correlation coefficient, coefficient of determination, partial t test, and simultaneous F test. Result. The research results show that: (1) Partially, there is a positive and significant influence between Work Motivation on Employee Performance, as evidenced by the correlation coefficient value of the Work Motivation variable (X1) of 0.687. and the calculated t value is 5.310 > t table 2.00488 with a significance of 0.000 < 0.05. (2) Partially, the non-physical work environment also has a positive and significant effect on employee performance, as indicated by a correlation coefficient value of 0.647, a coefficient of determination of 64.7%, and a calculated t value of 4.555 > t table 2.00488 with a significance of 0.000 < 0.05. (3) Simultaneously, Work Motivation and Non-Physical Work Environment have a positive and significant effect on Employee Performance, as shown by the multiple linear regression equation Y= 9.529 + 0.405 X1 + 0.370 and the calculated F value is 43.359 > F table 3.17 with a significance level of 0.000 < 0.05. Implication. Motivation and non-physical work environment affect employee performance, so the implication of this research is that companies are expected to increase work motivation, create a better work environment, and encourage employees to work more productively and with quality.